The short-term effect of rehabilitation on ecosystem services in the semi-arid succulent Karoo lowlands and the Little Karoo, South Africa - De Abreu, Petra (Department of Biological Sciences, 2014)
This study has shown that using active rehabilitation in combination with improved management strategies (e.g. rest from grazing) may induce recovery of certain ecosystem services within practically relevant time scales. However, these benefits might not be tangible for landowners or society as of yet, due to the small-scale nature of the rehabilitation application along with the relatively high, short-term associated costs. To alleviate financial constraints on farmers and in order to socially and financially enhance local communities, the focus for now should be on sourcing funds from government and private sectors for rehabilitation implementation.